2019
DOI: 10.3390/ijms20030552
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mast Cell Antibody-Targetable Cell Surface Protein Expression Profiles in Systemic Mastocytosis

Abstract: Despite recent therapeutic advances, systemic mastocytosis (SM) remains an incurable disease due to limited complete remission (CR) rates even after novel therapies. To date, no study has evaluated the expression on SM bone marrow mast cells (BMMC) of large panel of cell surface suitable for antibody-targeted therapy. In this study, we analyzed the expression profile of six cell-surface proteins for which antibody-based therapies are available, on BMMC from 166 SM patients vs. 40 controls. Overall, variable pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…[7][8][9][10][11][12] When involving the skin, neoplastic mast cells tend to have normal cytological features and do not differ from reactive mast cells; hence, we currently lack a specific marker for neoplastic mast cells in the skin, 13,14 in contrast with the well-known marker CD25 for neoplastic cells in the bone marrow. [15][16][17][18][19][20] Although several studies have shown that CD25 expression by mast cells in the skin was predictive of SM, [21][22][23] this immunostaining may not be applicable to CM. In fact, it has been shown that CD25 expression in the skin is not a reliable marker.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] When involving the skin, neoplastic mast cells tend to have normal cytological features and do not differ from reactive mast cells; hence, we currently lack a specific marker for neoplastic mast cells in the skin, 13,14 in contrast with the well-known marker CD25 for neoplastic cells in the bone marrow. [15][16][17][18][19][20] Although several studies have shown that CD25 expression by mast cells in the skin was predictive of SM, [21][22][23] this immunostaining may not be applicable to CM. In fact, it has been shown that CD25 expression in the skin is not a reliable marker.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, mast cells can release extracellular vesicles (exosomes) (Skokos et al, 2002, 2003) that could deliver regulatory molecules, including mtDNA and microRNAs (Kawikova and Askenase, 2014). Such microvesicles have been implicated in brain disorders (Tsilioni et al, 2014; Kawikova and Askenase, 2014) and pain disorders (Rafiee et al, 2018; Silva-Freire et al, 2019). We recently reported that extracellular vesicles are increased in the serum of children with ASD, contained mtDNA and stimulated cultured human microglia to secrete the pro-inflammatory molecules IL-1β and CXCL8 (Tsilioni and Theoharides, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CD2 expression was not detected on the surface of KIT D816V or control MC. CD33, a pan-myeloid marker also used as a criterion in SM disease diagnosis and a potential therapeutic cell surface target, was highly expressed in both, KIT D816V and control MCs ( Figure 2 F) [ 11 , 40 ].…”
Section: Resultsmentioning
confidence: 99%